2015
DOI: 10.1364/prj.3.0000b1
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dot lasers for silicon photonics [Invited]

Abstract: We review recent advances in the field of quantum dot lasers on silicon. A summary of device performance, reliability, and comparison with similar quantum well lasers grown on silicon will be presented. We consider the possibility of scalable, low size, weight, and power nanolasers grown on silicon enabled by quantum dot active regions for future short-reach silicon photonics interconnects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
98
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 173 publications
(100 citation statements)
references
References 48 publications
2
98
0
Order By: Relevance
“…[11][12][13] The distinctive zerodimensional density of states of QDs offers lower threshold current density with improved thermal stability in III-V lasers, 14 and their discrete localization promises greater immunity to defects associated with III-V/Si heteroepitaxy when compared to their conventional quantum-well counterparts. 15 More interestingly, these QDs are capable of bending or pinning the threading dislocations (TDs) because of their large strain field. 16,17 Recently, high performance electrically pumped continuous-wave InAs/GaAs QD lasers with an emission wavelength as long as 1315 nm have been directly grown on offcut silicon substrates, 11 yielding a low threshold current density of 62.5 A cm À2 , and an elevated operation temperature up to 120 C. These lasers have shown respectable operating lifetimes over 3100 h. To exploit the 1550 nm telecom wavelength where long-distance communication can benefit from the least attenuation, developing InP-based QD lasers on silicon is necessary.…”
mentioning
confidence: 99%
“…[11][12][13] The distinctive zerodimensional density of states of QDs offers lower threshold current density with improved thermal stability in III-V lasers, 14 and their discrete localization promises greater immunity to defects associated with III-V/Si heteroepitaxy when compared to their conventional quantum-well counterparts. 15 More interestingly, these QDs are capable of bending or pinning the threading dislocations (TDs) because of their large strain field. 16,17 Recently, high performance electrically pumped continuous-wave InAs/GaAs QD lasers with an emission wavelength as long as 1315 nm have been directly grown on offcut silicon substrates, 11 yielding a low threshold current density of 62.5 A cm À2 , and an elevated operation temperature up to 120 C. These lasers have shown respectable operating lifetimes over 3100 h. To exploit the 1550 nm telecom wavelength where long-distance communication can benefit from the least attenuation, developing InP-based QD lasers on silicon is necessary.…”
mentioning
confidence: 99%
“…These devices were directly compared with simultaneously fabricated QW lasers with an identical TD density showing that QW devices were incapable of lasing at all at these TD densities. 38 Further testing of the same devices showed extrapolated lifetimes of 4600 h at aging conditions of 30 • C and more than twice the threshold. 39 These performance results and later results by Chen et al in 2016 showing 62.5 A/cm 2 current densities and extrapolated lifetimes >100 000 h at relaxed conditions 40 began to make the case that QD lasers grown on Si can be a commercial technology.…”
Section: Apl Photonics 3 030901 (2018)mentioning
confidence: 93%
“…A detailed study of the effects on lasers using simultaneously processed QD and QW materials showed that while all the QW devices on Si failed to lase, the devices with QDs lased with low thresholds and high output powers. 38 Additionally, the photoluminescence of the as-grown material showed only a 20% reduction in intensity for the QDs as compared to a 90% reduction for QWs. The reduced sensitivity to defects has also allowed for commercially promising extrapolated lifetimes to be realized in epitaxial lasers at >10 000 000 h. 51 Figure 13(a) shows the extrapolated mean-time-to-failure, defined as a doubling of the threshold current, versus aging time for lasers with varying dislocation density.…”
Section: G Defect Tolerancementioning
confidence: 98%
See 1 more Smart Citation
“…The active laser structures were grown on a GaAs-on-V-grooved-Si (GoVS) template 9 that is free of antiphase-domains and absorptive intermediate buffers. Compared to the quantum dot lasers recently demonstrated on offcut silicon using Ge buffers, [10][11][12][13][14] or direct nucleation of GaAs, 15,16 the use of on-axis (001) silicon offers better compatibility with conventional Si CMOS processes. The promising lasing characteristics of the MDLs also suggest a viable route towards large-scale, lowcost integration with passive optical components on a silicon-on-insulator (SOI) platform.…”
mentioning
confidence: 99%